2012
DOI: 10.1209/0295-5075/99/17008
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism and magnetization reversal in YFe 1−x Cr x O 3

Abstract: We present combined experimental and theoretical studies on the magnetic properties of a solid solution between yttrium orthoferrite and yttrium orthochromite systems, YFe1−xCrxO3 (0 ≤ x ≤ 1) where Fe 3+ and Cr 3+ ions are distributed randomly at the same crystallographic site (4b). We found that all the compositions exhibit weak ferromagnetism below the Néel temperature that decreases non-linearly with increasing x, while certain intermediate compositions (x = 0.4, 0.5) show a compensation point and magnetiza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 27 publications
5
50
0
Order By: Relevance
“…One of the members of the rare-earth orthochromite family, YCrO 3 does not exhibit dielectric anomaly or ferroelectric polarization at the magnetic transition. By introducing cation disorder at the Cr-site, Mao found weak ferromagnetism below the Ne´el M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT temperature (T N ) and high temperature multiferroicity in YFe 0.5 Cr 0.5 O 3 [9,10]. Later, Rajeswaran reported that RCr 0.6 Mn 0.4 O 3 (R= Y, La, Lu) exhibit ferroelectric polarization at T N [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of the members of the rare-earth orthochromite family, YCrO 3 does not exhibit dielectric anomaly or ferroelectric polarization at the magnetic transition. By introducing cation disorder at the Cr-site, Mao found weak ferromagnetism below the Ne´el M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT temperature (T N ) and high temperature multiferroicity in YFe 0.5 Cr 0.5 O 3 [9,10]. Later, Rajeswaran reported that RCr 0.6 Mn 0.4 O 3 (R= Y, La, Lu) exhibit ferroelectric polarization at T N [6].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental observations of exchange bias field in oxide coated cobalt and magnetization reversal in cobalt vanadate (IV) are known for a long time. 20,21 Recently, MR has been reported in several other systems such as Sr 2 RRuO 6 (R ¼ Yb, Y), 17,22,23 orthovanadates, 18,[24][25][26][27] orthoferrites, [28][29][30] orthochromites, [31][32][33][34][35][36][37][38][39][40][41] perovskite manganites, [42][43][44] and molecular magnets. [45][46][47] The mechanism of MR is found to be quite different in different systems.…”
Section: Introductionmentioning
confidence: 99%
“…Substitutions on rare earth site using other rare earth elements and on Cr site using other transition elements give rise to interesting properties like magnetization reversal (MR) and exchange bias (EB) phenomena. Even though MR is known to appear in ferrimagnetic (FIM) compounds [7], recently many other compounds such as Sr 2 YbRuO 6 [8], orthochromites [5,[9][10][11][12][13][14][15][16][17][18][19][20][21], orthoferrites [22][23][24], othovanadates [25,26], molecular magnets [27,28] and intermetallic alloys [29,30] are shown to exhibit such behavior. Exchange bias phenomenon has been studied in heterostructure of bilayer/multilayer thin films of AFM/FM, AFM/FIM (ferrimagnetic), AFM/SG (spin glass), etc.…”
Section: Introductionmentioning
confidence: 99%